The mutillid wasps of the Dasymutilla paradoxa species-group (Hymenoptera, Mutillidae) - Luz, David R.; Williams, Kevin A.; Bartholomay, Pedro R. (Zootaxa, 2016)
The Dasymutilla paradoxa species-group is newly proposed to include taxa formerly included in the genera Dasymutilla Ashmead, 1899, Traumatomutilla André, 1901 and some previously incertae sedis. This species-group now includes the following eight species: D. fasciventris Mickel, D. guanacaste Manley & Pitts, D. naranjo Manley & Pitts, D. paradoxa (Gerstaecker), comb. nov., D. paraparadoxa, sp. nov., D. phya (Cameron), comb. nov., D. relata (Cameron), and D. sliepniri Manley & Pitts. Dasymutilla paraparadoxa Luz, Bartholomay & Williams, sp. nov. (Mexico, Guatemala) is described and illustrated. New synonymy is proposed (valid names are first) for: Dasymutilla fasciventris Mickel, 1938 (=Dasymutilla citromaculosa Manley & Pitts, 2007, syn. nov., =Dasymutilla chamela Manley & Pitts, 2007, syn. nov.); Mutilla paradoxa Gerstaecker, 1874 (=Sphaerophthamla [sic!] icaris Cameron, 1895, syn. nov.); Sphaerophthalma [sic!] phya Cameron, 1895 (=Sphaerophthalma [sic!] melissa Cameron, 1895, syn. nov.). The key to species is given.